Pengaruh Lingkungan Keluarga Terhadap Kedisiplinan Siswa pada Pembelajaran PAI di MI - Faizatul Khoeriyah (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2022)
In the educational process, generally a discipline must be owned by every student because with discipline a person can increase his ability to protect himself from something that causes confusion. Discipline cultivation must be done early. If discipline is instilled in the family environment from an early age, they will make it a habit and part of themselves. The level of discipline of each student is different, depending on how parents provide guidance to their children and how education is in their family environment. This study aims to examine in depth the influence of the family environment on student discipline. This type of research is field research using a quantitative approach and taking the subjects of MI Salafiyah Tanjung students. There is a population of 276 students and the sample is 45 students out of 6 (purposive sampling). The data were collected using a Likert scale questionnaire statement. The results of the data are processed through statistical calculations from preliminary analysis, prerequisite tests, and hypothesis testing using SPSS V.26. Obtained very high family environment data of 68.13, very high student discipline of 72.51, and R Square results of 39.1%. Overall, it can be seen from the acquisition of R Square results of 39.1% which means that there is a family influence on student discipline of 39.1% and 60.9 is influenced by other variables.